Job motivation level based on Maslow’s hierarchy of needs among foreigners in Malaysia / Muhammad Hafeez Khan Yusoff Khan and Khairil Adlil Kamil - Yusoff Khan, Muhammad Hafeez Khan; Kamil, Khairil Adlil (Faculty of Business and Management, Universiti Teknologi MARA, 2014)
Individual’s behaviour is basically goal oriented and individuals’ needs differ from one another. Maslow came up with this theory on hierarchy of needs in 1943 based on deficiency and growth needs. He arranged human needs in ascending order of physiological needs until the need for self-actualization. The hierarchy of needs’ theory as propounded by Maslow may not be applicable as perceived by foreigners in Malaysia because many individuals seem to act on their perception of reality. There is a concern that needs and motivation will deviate from Maslow’s hierarchical order. There is need to investigate these assertions to find out if the foreigners would perceive their needs as being in Maslow’s. The hierarchy of needs’ theory as propounded by Maslow may not be applicable as perceived by foreigners in Malaysia because many individuals seem to act on their perception of reality. There is a concern that needs and motivation will deviate from Maslow’s hierarchical order. Thus, there is a need to investigate these assertions to find out if the foreigners would perceive their needs as being in Maslow’s. By analyzing data gathered from 100 respondents made of foreign workers in various industries, results shows that there is no difference in perception perspective between male and female foreigners in Malaysia. Moreover, most foreigners in Malaysia have achieved until esteem level and the relationship of all the variable are mostly weak and very weak.